Bioactive Compounds from Agricultural Residues, Their Obtaining Techniques, and the Antimicrobial Effect as Postharvest Additives - Rafael Gomes-Araújo; Dolores Gabriela Martínez-Vázquez; Ana Verónica Charles-Rodríguez; Sarahi Rangel-Ortega; Armando Robledo-Olivo (International Journal of Food Science)
Agricultural vegetable products always seek to meet the growing demands of the population; however, today, there are great losses in supply chains and in the sales stage. Looking for a longer shelf life of fruits and vegetables, postharvest technologies have been developed that allow an adequate transfer from the field to the point of sale and a longer shelf life. One of the most attractive methods to improve quality and nutritional content and extend shelf life of fruits and vegetables is the incorporation of bioactive compounds with postharvest technologies. These compounds are substances that can prevent food spoilage and the proliferation of harmful microorganisms and, in some cases, act as a dietary supplement or provide health benefits. This review presents an updated overview of the knowledge about bioactive compounds derived from plant residues, the techniques most used for obtaining them, their incorporation in edible films and coatings, and the methods of microbial inhibition.